PERAN AL-JINĀS DALAM AL-TAFSĪR AL-BAYĀN LI AL-QUR’ĀN AL-KARĪM KARYA AISYAH ABD AL-RAHMAN BINT AL-SYATI’ - Miftahul Jannah; Muhammad Harjum; Andi Miswar (IMTIYAZ: Jurnal Ilmu Keislaman, 2026)
This study aims to analyze the role of al-jinās in al-Tafsīr al-Bayān li al-Qur’ān al-Karīm by Bint al-Syāṭi’ and to explain its function in the construction of the meaning of Qur’anic verses. Studies of al-jinās have generally focused on its classification and rhetorical beauty, while its role in the process of interpretation has received relatively little anttantion. This is a literature review using a qualitative approach. Primary data is sourced from Al-Tafsīr al-Bayān li al-Qur’ān al-Karīm by Bint al-Syāṭi’, while secondary data is obtained from Bint al-Syāṭi’s works, balagha literature, and relevant previous studies. Analysis was conducted through the identification of al-jinās forms, the classification of their types, and an examination of Bint al-Syāṭi’s interpretation of verses containing al-jinās. The research findings indicate that Bint al-Syāṭi’ does not view al-jinās as an independent aesthetic phenomenon, but rather as a linguistic device that reveals the semantic relationship between words within a verse. Sound similarity in al-jinās functions as an interpretive cue that directs the reading toward semantic relationship, whether in the form of emphasis or interconnections between ideads. This finding indicates a close connection between the phonological and semantic aspects in Bint al-Syāṭi’s adabī exegesis and confirms that al-jinās contributes to the formation of meaning in the Qur’an